Public speaking strategies for success - Zarefsky, David (Pearson Education, 2008)
At all stages of the public speaking process, readers learn how to develop and apply strategies to speaking situations they encounter throughout their lives. Zarefsky urges readers to consider the diversity of audiences, occasions, and speakers and to choose a specific purpose, a relevant topic, and the appropriate material to make their speeches successful.